Determination of uncertainty profiles in neutral atmospheric properties measured by radio occultation experiments. Issue 8 (15th October 2022) - Bourgoin, A.; Gramigna, E.; Zannoni, M.; Gomez Casajus, L.; Tortora, P.
Abstract: Radio occultations are commonly used to assess remotely the thermodynamic properties of planets or satellites' atmospheres within the solar system. The data processing usually involves the so-called Abel inversion method or the numerical ray-tracing technique. Both these approaches are now well established, however, they do not allow to easily determine the uncertainty profiles in the atmospheric properties, and this makes the results difficult to interpret statistically. Recently, a purely analytical approach based on the time transfer functions formalism was proposed for modeling radio occultation data. Using this formulation, we derive uncertainty relationships between the frequency shift and the thermodynamic properties of the neutral atmosphere such as the temperature, pressure, and neutral number density. These expressions are important for interpreting previous results from past radio occultation experiments. They are especially relevant for deriving the system requirements for future missions in a rigorous manner and consistently with the scientific requirements about the atmospheric properties retrieval.